PPI inflation rate from 1% to 6% – Mathematical Reasoning of Economic Intervening Principle Based on Yin Yang Wu Xing Theory in Traditional Chinese Economics (II) - Zhang, Yingshan (Advances in Social Sciences Research Journal, 2020)
PPI (Producer Price Index) is useful in understanding industry economic disease. By using mathematical reasoning based on Yin Yang Wu Xing Theory in Traditional Chinese Economics (TCE) or Traditional Chinese Science (TCS), this paper demonstrates that for the PPI inflation rate of industry economic society, the normal range of theory is nearly to . The first or second transfer law of economic diseases changes according to the different PPI inflation rate whether in the normal range or not. The treatment principle:“Don’t have economic disease cure cure non-ill” () is abiding by the first or second transfer law of economic diseases. Assume that the range of PPI inflation rate is divided into four parts from small to large. Both second and third are for a healthy economy. Our works are the prevention or treatment for a more serious relation economic disease which comes from the first transfer law. And both first and fourth are for an unhealthy economy. Our works are the prevention or treatment for a more serious relation economic disease which comes from the second transfer law. Economic disease treatment should protect and maintain the balance of two incompatibility relations: the loving relationship and the killing relationship.